PENERAPAN RESTORATIVE JUSTICE BAGI ANAK KORBAN TINDAK PIDANA PERKAWINAN DIBAWAH UMUR - Lestari, B. Farhana Kurnia; Megayati, Dhina (Nusantara Hasana Journal, 2022)
Restorative justice is a way of handling child criminal cases outside the formal legal channels to guarantee and respect the dignity of the child, as well as the interests of the child and pay attention to justice for the victim. Restorative justice is a process in which all parties with an interest in a particular violation meet together to resolve jointly for the sake of the future. Restorative justice aims to empower victims, perpetrators, families, and communities to correct an act against the law by using awareness and conviction as a basis for improving community life. The application of Restorative Justice to Children Victims of Underage Marriage Crimes is one of them by implementing the Juvenile Criminal Justice System (SPPA). By focusing on the accountability of perpetrators to victims of criminal acts through a Restorative approach.